2013
DOI: 10.1200/jco.2011.41.0902
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of Tumor-Infiltrating Lymphocytes in a Phase III Randomized Adjuvant Breast Cancer Trial in Node-Positive Breast Cancer Comparing the Addition of Docetaxel to Doxorubicin With Doxorubicin-Based Chemotherapy: BIG 02-98

Abstract: In node-positive, ER-negative/HER2-negative BC, increasing lymphocytic infiltration was associated with excellent prognosis. Further validation of the clinical utility of tumor-infiltrating lymphocytes in this context is warranted. Our data also support the evaluation of immunotherapeutic approaches in selected BC subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

75
1,081
7
14

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,419 publications
(1,221 citation statements)
references
References 34 publications
75
1,081
7
14
Order By: Relevance
“…109 In the Breast International Group 2-98 trial, retrospective-prospective analyses detected a positive correlation between the number of TILs and survival in TNBC. 110 The presence of TILs is also associated with increased pathological complete response (pCR) rates. The first randomized controlled trial indicated that a relationship exists between increased numbers of TILs and pCR rates.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
“…109 In the Breast International Group 2-98 trial, retrospective-prospective analyses detected a positive correlation between the number of TILs and survival in TNBC. 110 The presence of TILs is also associated with increased pathological complete response (pCR) rates. The first randomized controlled trial indicated that a relationship exists between increased numbers of TILs and pCR rates.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
“…TME can influence both cancer progression and therapeutic responses (McMillin et al ., 2013; Quail and Joyce, 2013), and tumor‐related inflammation is now recognized as a hallmark of cancer (Hanahan and Weinberg, 2011). The tumor's immunological portrait – the presence of tumor‐infiltrating leukocytes, their nature, and the profile of regulatory cytokines – is determinative for BC outcome and therapeutic response (Fridman et al ., 2012; Loi et al ., 2013). Good outcome/response is associated with a high fraction of cytotoxic T cells and assisting T‐helper 1 cells, whereas poor outcome/resistance is linked to the dominance of T‐helper 2 cells and tumor‐associated macrophages (TAMs) (Savas et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1) [16-18, 21-23, 33, 34]. Of these, 4 RCTs (1,694 patients) [21][22][23]33] were conducted in the neoadjuvant setting and 4 RCTs (3,820 patients) [16][17][18]34] were conducted in the adjuvant setting. Selected arms of neoadjuvant trials and their characteristics are listed in Table 1.…”
Section: Selected Trialsmentioning
confidence: 99%
“…Three RCTs (2,132 patients) [17,18,34] included an arm with luminal disease subtype, 3 RCTs (618 patients) [17,18,34] included an arm with HER2-positive disease, and 4 RCTs (1,070 patients) [16][17][18]34] included an arm with TNBC.…”
Section: Selected Trialsmentioning
confidence: 99%
See 1 more Smart Citation